A Need for Pharmacovigilance in OTC Steroid Misuse: Real-World Insights - Karthikesan, Jayasri (Indian Journal of Pharmacy Practice)
Over-the-Counter (OTC) corticosteroid misuse remains a pressing yet underreported issue in rural India. This letter presents a case of a 70-year-old male who developed iatrogenic Cushing’s syndrome complicated by urosepsis and septic shock after prolonged self-medication with dexamethasone. The case underscores the urgent need for enhanced pharmacovigilance systems at the community level, stricter enforcement of Schedule H regulations, and the active involvement of pharmacists in identifying and preventing such adverse drug reactions. Strengthening public awareness and pharmacist-led interventions are vital to curb the inappropriate use of potent corticosteroids.
Keywords: Over-the-counter drugs; Corticosteroids; Pharmacovigilance; Schedule H violations; Rural healthcare